Access to acute stroke care: a description of stroke patients' journey to a district hospital - O'Meara, Ryan Mark (Department of Medicine, 2025)
Introduction The burden of stroke in Africa has increased in the last two decades, with the population undergoing a rapid epidemiological transition, with a rise in the incidence of stroke risk factors together with the gradual aging of the population. Evidence-based guidelines for acute stroke care are often not feasible in resource challenged settings but even when resources are available, considerable delays to definitive care exists. This study aims to describe the factors that influence time from symptom onset to hospital arrival in patients that present to a district level hospital Emergency Centre with confirmed ischaemic strokes. Methods A descriptive analysis was performed using retrospective folder and database review. All adult patients with a confirmed ischaemic stroke presenting to Mitchells Plain Hospital Emergency Centre during the study period of 12 months (1st of January 2019 to 31st of December 2019), were eligible for inclusion. Data were collected from existing electronic patient databases and the time from onset of symptoms to hospital arrival was extracted from the clinical notes. Results A total of 730 (2%) patients presented with a diagnosis of stroke, of which 381 (52%) were included (CT confirmed ischaemic strokes). Only 48 (13%) presented within 4.5 hours of symptom onset and the median time from onset of symptoms to presentation to the hospital was 24 hours (IQR 12-72 hours). The majority of patients (31%) arrived via a primary public emergency medical service (EMS) call, while 29% presented directly to the hospital as self-referrals with private transport. Primary public EMS calls had the shortest call-to-hospital-arrival time (1 hour and 31 minutes), even though the median time from symptom onset to hospital arrival was still 16 hours. Conclusion The median time from symptom onset to hospital arrival for patients with stroke symptoms is much longer than what evidence-based guidelines suggest. The chain of survival for emergency stroke care is only as strong as its weakest link and the data from this study suggest that improvement campaigns should target stroke education and access to care.